Patterns of Developing Madrasah as Islamic Elite Education Institutions - Fathorrahman, Fathorrahman (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2018)
Historically madrasas are type of education characterized by Islam, in addition to pesantren. The presence of madras in Indonesian Muslim community is counter modern educational institutions managed by the Colonial. With madras, it can reduce the unemployment rate of rural children who are economically unable to enter the modern schools. Even though we recognize it in quality, madrasas are not as grand and as good as the Colonial Government's schools, but at least help Muslim children to go to formal education. By looking at the demands of society today, madrasas are required to balance even they can exceed the demands or desires of the community. This is the reason why this research was conducted, namely to look at madrasas and their development patterns in this global era. Through regulation in order to advance the madrasa, because of the government's enormous contribution to the development of madrasas in Indonesia. The results of this study indicate that early madrasas stood alone, until then the new independent Indonesia madrasas received attention from the government, and attention was dynamic with regulations. New regulations, in order to advance madrasas both in quantity and quality